Mechanistic Insights into the Ferroptosis-Regulating Effects of EF in the Treatment of Chronic Renal Failure - Zhang, Qian; Xv, Xinran; Zhang, Wanchuan; Yang, Xiang; Li, Jincai; Li, Tiejun (Current Medicinal Chemistry, 2026)
IntroductionChronic Renal Failure (CRF) is a progressive disease that severely affects patients' quality of life, but its current treatment options remain limited. This study explores the potential mechanism of Eriobotryae Folium (EF) in treating CRF by targeting ferroptosis.MethodsActive compounds and targets of EF were identified through multiple databases (TCMSP, SwissTargetPrediction, UniProt, GeneCards, DrugBank). Using Cytoscape and STRING, both a compound-target network and a PPI network were generated. GO and KEGG analyses were conducted to explore relevant biological functions and pathways. The binding affinity and stability between critical compounds and target proteins were investigated through molecular docking and Molecular Dynamics (MD) simulations.ResultsEighteen active compounds and 366 targets of EF were identified, along with 1,267 CRF-related and 1,673 ferroptosis-related targets, with 40 overlapping genes. PPI analysis highlighted AKT1, EGFR, HIF1A, SRC, and ESR1 as key targets. The KEGG analysis indicated MAPK and HIF-1 pathways as major regulatory pathways. Molecular docking suggested quercetin, ellagic acid, and oleanolic acid as potential active compounds, with EGFR and SRC as promising targets. MD simulations confirmed strong and stable binding, especially for EGFR-ellagic acid (-21.38 kcal/mol) and EGFR-oleanolic acid (-24.02 kcal/mol).DiscussionThis study suggests that EF treats CRF by targeting ferroptosis-related pathways and key proteins, such as EGFR and AKT1. MAPK and HIF-1 signaling pathways further substantiate its significant role in disease regulation.ConclusionEF may regulate ferroptosis through multiple targets and pathways, offering potential therapeutic benefits for CRF. The findings offer foundational insights for subsequent research and therapeutic development.
Keywords: ferroptosis